Ответ:
Объяснение:
№9.4
1) √√3= ⁴√3 2)√∛4= ⁶√4
№9.5
1)⁴√2 × ⁴ √3 / ⁴√486 + ∛(27×2⁶) = ⁴√6 /⁴√486 +∛27×∛2⁶ = ⁴√(6/486) +3×2²= ⁴√(1/81) +3×4= 1/3 +12= 12 1/3 (12 целых одна третья)
2)∛(216×7³) - ⁵√(32/243) =∛216 ×∛7³ - ⁵√32 /⁵√243= 6×7 - 2/3 = 42 -2/3 = 41 1/3 (сорок одна целая одна третья)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
№9.4
1) √√3= ⁴√3 2)√∛4= ⁶√4
№9.5
1)⁴√2 × ⁴ √3 / ⁴√486 + ∛(27×2⁶) = ⁴√6 /⁴√486 +∛27×∛2⁶ = ⁴√(6/486) +3×2²= ⁴√(1/81) +3×4= 1/3 +12= 12 1/3 (12 целых одна третья)
2)∛(216×7³) - ⁵√(32/243) =∛216 ×∛7³ - ⁵√32 /⁵√243= 6×7 - 2/3 = 42 -2/3 = 41 1/3 (сорок одна целая одна третья)